Secretin: a hormone for HCO3− homeostasis - Berg, Peder; Svendsen, Samuel L.; Ayasse, Niklas; Sorensen, Mads Vaarby; Leipziger, Jens (Pflügers Archiv, 2024)
Secretin is a key hormone of the intestinal phase of digestion which activates pancreatic, bile duct and Brunner gland HCO3− secretion. Recently, the secretin receptor (SCTR) was also found in the basolateral membrane of the beta-intercalated cell (B-IC) of the collecting duct. Experimental addition of secretin triggers a pronounced activation of urinary HCO3− excretion, which is fully dependent on key functional proteins of the B-IC, namely apical pendrin and CFTR and the basolateral SCTR. Recent studies demonstrated that the SCTR knock-out mouse is unable to respond to an acute base load. Here, SCTR KO mice could not rapidly increase urine base excretion, developed prolonged metabolic alkalosis and exhibited marked compensatory hypoventilation. Here, we review the physiological effects of secretin with distinct focus on how secretin activates renal HCO3− excretion. We describe its new function as a hormone for HCO3− homeostasis.